Study of the functional 3d heart model using soft materials flexible thermoplastic polyurethane (TPU FLEX SHORE 95 A) and elastic photopolymer resin (EPP SHORE 40 A) for cardiovass monitoring device - Nur Afikah, Khairi @ Rosli (2022)
Nowadays, advancements in technology and engineering are widely applied in the medical healthcare sector. However, based on the present study, studies are still limited on the mechanical properties of elastomers, particularly thermoplastic polyurethane and elastic photopolymer resin as used in the development of heart models. Besides, there are minimal studies on the production of cardiac models in Malaysia. In addition, the difficulties faced by medical practitioners in understanding the coronary artery disease blockage situation and flow drawbacks due to the formation of plaques are also a major concern. Thus, this research was initiated to determine the mechanical properties of selected materials, flexible thermoplastic polyurethane (TPU flex shore 95 A) and elastic photopolymer resin (EPP shore 40 A) in the development of heart models. With regards to the study method, the mechanical properties of these soft materials were investigated through the strength test, hardness test, and fractography test. The fused deposition modeling (FDM) and stereolithography (SLA) methods were employed to create the functional 3D heart model. The physiological characteristics of blood flow on the 3D heart model were also well observed. The results suggested that the TPU flex possessed higher strength (8.81±0.003 MPa) and elasticity (34.69±0.288 MPa) compared to the EPP ((1.29±0.002 MPa (strength), 8.97±0.012 MPa (elasticity)) material. Additionally, the functional 3D heart model using soft materials for the cardiovascular simulator (CardioVASS) device was well developed. Then, the physiological flow of the heart model was able to successfully emulate the consequences of having coronary artery disease, where the highest percentage of blockage resulted in the most severe blood flow obstruction (20%, 40%, 60% and 90%). In conclusion, the development of the functional 3D heart model for the purpose of the CardioVASS device has been successfully implemented by determination of the TPU flex and EPP material mechanical properties, fabrication of the functional heart model and investigation regarding physiological characteristics of blood flow were finally achieved.